Development of a three-step hybrid simulation approach (THSA) for engine combustion investigation coupled with a multistep phenomenon soot model and energy balance analysis. (1st January 2017) - Yu, Wenbin; Yang, Wenming; Zhao, Feiyang; Zhou, Dezhi; Tay, Kunlin; Mohan, Balaji
Highlights: A three-step hybrid simulation approach was proposed for engine combustion investigation. A multi-step phenomenon soot model was coupled into the three-step hybrid simulation approach. The energy balance analysis was coupled into the three-step hybrid simulation approach. KIVA4 and CHEMKIN II codes were coupled to solve the detailed chemical reactions for engine combustion. Abstract: A comprehensive simulation approach is important in order to better replicate the complex combustion process over a wide range of engine operating conditions. This will allow a more accurate understanding of crucial factors that affect engine combustion. In this study, the entire engine combustion process was systematically considered and a three-step hybrid simulation approach (THSA) was proposed in order to achieve a more accurate engine combustion simulation. For this approach, a so-called "full cavitation" model was selected for 3-dimensional (3D) internal nozzle flow study and a Kelvin-Helmholtz/Rayleigh-Taylor (KH-RT) model was used for 3D spray prediction wherein the flow variables at the nozzle outlet obtained through internal nozzle flow simulations were used as the input information in the KIVA4 code. Besides, a compact and accurate primary reference fuel (PRF) mechanism with 46 species and 144 reactions, which is coupled with a multi-step phenomenon soot model and energy balance analysis, was used for engine combustion simulation. Based on it, a numerical study was conducted for a comparison between conventional direct injection combustion (CDIC) and partially premix combustion (PPC) fueled with diesel, gasoline and diesel/gasoline blend fuel (GD). The final result indicates that with PPC and gasoline fuel, an optimized and high thermal efficiency of 52.5% can be realized along with extremely low NOx and soot emissions.